(3GdeMGSHI GdeJhSWI (B/s - (3GdLHhQj, aDGO YHO GdeMSfs ((3YeGf(B: s (3OGQ GdGjGe(B, s, 2015)
(3jVe GdEWGQ GdeaGgej ddeMGSHI, GdMSGHGJ GdNJGejI h GdcThaGJ GdeGdjI aj GdefTBJ GdJLGQjI h GdUfGYjI, GdJShjGJ GdbjOjI h ChQGb GdYed, GdCNWGA GdeMGSHI h cjajI JUMjMgG, GdfbOjI hGdGSJKeGQGJ bUjQI GdGLd , GdeOjfhf hGdeNRhf GdSdYj, GdESJKeGQGJ WhjdI GdGLd (B((3GdSfOGJ(B) (3, GdehLOGJ ZjQ GdeJOGhdI hGfOKGQGJgG, bGFeI GdJOabGJ GdfbOjI, GdehLOGJ ZjQ GdedehSI(B((3GdeYfhjI(B).s
(3GdeUGOQ U(B.249s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeMGSHIs; (3JObjb GdMSGHGJs